Raport Gizi Untuk Mencegah Stunting Di Paud Melati Des. Pungka, Kec. Unter Iwes, Kab. Sumbawa - Has’ad Rahman Attamimi; Yunita Lestari (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
The problem of children with stunted growth is a condition in which one of the contributing factors is a nutritional problem. All over the world, especially in countries with high poverty rates, this case is not difficult to find. Stunting is considered a problem because it has a relationship with the risk of morbidity and mortality. According to WHO, Stunting is the result of standard growth not reaching -2 standard deviations which is assessed from the Z-score of body length for age (PB/U) or height for age (TB/U). To deal with the stunting problem, assistance is needed from the community, including religious leaders, traditional leaders, community leaders, the government, institutions, Family Welfare Development (PKK), youth organizations, posyandu cadres, doctors, midwives, Early Childhood Education teachers (PAUD) and the community who care for health and education play an active role in monitoring all editing targets in the First Thousand Days of Life (1,000 HPK). Unter Iwes Kab. Sumbawa by implementing the Nutrition Report Card. It is hoped that the application of the Nutrition Report Card can become a medium of communication between the Community Service Executor, the School, and the community (student parents), so that information on the child's nutritional status is obtained in an updated manner, as well as for the implementation of Community Service has an overview in determining the follow-up steps to be taken. In addition, the implementation of the Nutrition Report Card is also carried out as a form of efforts to prevent and reduce stunting, especially in the Pungka Village area, Kec. Unter Iwes Kab. Sumbawa.